Doing Q methodological research theory, method and interpretation - Watts, Simon 1967-; Stenner, Paul (SAGE, 2012)
This book is a simple yet thorough introduction to Q methodology, a research technique designed to capture the subjective or first-person viewpoints of its participants. Watts and Stenner outline the key theoretical concepts developed by William Stephenson, the founder of Q methodology, including subjectivity, concourse theory and abduction. They then turn to the practicalities of delivering high quality Q methodological research.